St. Boniface, Scipio, Anderson County - Stevenson, Matthew (Kansas State University, The Chapman Center for Rural Studies, 2011)
This is a study of the origins of St. Boniface Parish. The author takes you from the early beginnings founded by Jesuit missionaries as a territorial Catholic church serving displaced native Americans to a 600 acre subsistence farm and monastery run by the Carmelite Friars serving the German immigrants. St. Boniface still operates as a parish today and is located in the North of Anderson County, Kansas; just two miles East of highway 59 on 2350 road.
Matthew Stevenson, “St. Boniface, Scipio, Anderson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/13.
Keywords: Anderson County; Carmelite; Jesuit Missionaries; Pottawatomie Valley; Scipio; St.Boniface